Anterior Skull Base Meningioma: Surgical Approach and Complication Avoidance - Nangarwal, Bhawan; Gosal, Jaskaran Singh; Das, Kuntal Kanti; Khatri, Deepak; Bhaisora, Kamlesh; Verma, Pawan Kumar; Sardhara, Jayesh; Mehrotra, Anant; Srivastava, Arun K.; Jaiswal, Awadhesh K.; Behari, Sanjay (Journal of Neurological Surgery Part B: Skull Base, 2022)
Introduction Endoscopic endonasal approach (EEA) and keyhole transcranial approaches (TCAs) are being increasingly used in anterior skull base meningioma (ASBM) surgery.Objective We compare tumor resection rates and complication profiles of EEA and supraorbital keyhole approach (SOKHA) with conventional TCAs.Methods Fifty-four patients with ASBM (olfactory groove meningioma [OGM], n = 19 and planum sphenoidale/tuberculum sellae meningioma [PSM/TSM], n = 35) operated at a single center over 7 years were retrospectively analyzed.Results The overall rate of gross total resection (GTR) was higher in OGM (15/19, 78.9%) than PSM-TSM group (23/35, 65.7%, p = 0.37). GTR rate with OGM was 90% and 75% with TCA and EEA. Death (n = 1) following medical complication (TCA) and cerebrospinal fluid leak requiring re-exploration (n = 2, one each in TCA and EEA) accounted for the major complications in OGM. For the PSM/TSM group, the GTR rates were 73.3% (n = 11/15), 53.8% (n = 7/13), and 71.4% (n = 5/7) with TCA, EEA, and SOKHA, respectively. Seven patients (20%) of PSM-TSM developed major postoperative complications including four deaths (one each in TCA and SOKHA, and two in EEA groups) and three visual deteriorations. Direct and indirect vascular complications were common in lesser invasive approaches to PSM-TSM especially if the tumor has encased intracranial arteries.Conclusion No single approach is applicable to all ASBMs. TCA is still the best approach to obtain GTR but has tissue trauma-related problems. SOKHA may be a good alternative to TCA in selected PSM-TSMs, while EEA may be an alternate option in some OGMs. A meticulous patient selection is needed to derive reported results of EEA for PSM-TSM.
Keywords: minimally invasive; supraorbital keyhole; endoscopic endonasal; transcranial; skull base approach; anterior skull base meningioma; complications; arterial injury